Frequency of Various Causative Bacterial Organisims and their Culture Sensitivity Pattern in Patients with Open Tibial Fracture - Rasheed Ahmed Bhatti, Muhammad Rafique Jakhrani, Asif Ali Shaikh, Asad Hanif Shaikh, Irshad Ahmed Bhutto, Muhammad Waliullah Qureshi (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of various causative bacterial organisms and their culture sensitivity pattern in patients with open tibial fracture. Subject and Methods: This is cross sectional study conducted at Orthopedic Surgery, Liaquat University of Medical and Health Sciences, Jamshoro and SMBBMU Larkana from 14th October 2015 to 13th April 2016. Total of 150 patients having open tibial fracture with signs and symptoms of infections presenting within one week of fracture were included in this study. All this information was recorded through Proforma (attached). Results: Out of 150 infected fractures, S. aureus was present in 40% cases, MRSA in 14%, Enterococcus in 4%, B-Staphylococcus in 4%, Pseudomonas aeruginosa in 8%, Acinetobacter in 4%, E.coli in 16% and Klebsiella in 10%. Regarding sensitivity analysis, Meronem, Pipericillin, Avelox, Linzulid were more than 80% sensitive to S. Aureus. MRSA Enterococcus Sp, B-Streptococcus. Ceftazidime, Gentamicin were more than 80% sensitive to S. Aureus and gentamicin also 83.3% sensitive to B-Streptococcus. Gentamicin was 83.3% sensitive to Enterococcus Sp as shown in table 2A. Meronem, Pipericillin were 80% to 96% sensitive to Pseudomonas aeruginosa, Acinetobacter, E. Coli and Klebsiella Species. Avelox was 83.3% sensitive to Pseudomonas aeruginosa. Ceftriaxone and Avelox were 87.5% and 100% sensitive to E. coli. Conclusion: It is noted that infection rate is higher in open fracture mostly fracture at extremity of bones. More severe and exposure, more is infection rate noted.